Homeless persons and villages: drugs, social marginalization, and territory of care - Aline Basso da Silva; Agnes Olschowsky; Cristiane Kenes Nunes; Fabrício Soares Braga; Mariane da Silva Xavier Botega (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to recognize villages as territories of care and daily resistance to social marginalization. Methods: a descriptive study with a qualitative approach based on the methodological framework of ethnography inspired by Interpretative Anthropology. Two-year field research (from the second half of 2015 to the first half of 2017). Participant observation and semi-structured interviews with four privileged interlocutors and a field diary have been used. Data systematization was carried out throughout field work. Results: three categories emerged: Interlocutors talking about their life in villages; Villages as a care device; and Drugs in villages. Final considerations: the results reveal the challenge for health and nursing to recognize the need to understand the contexts of urban life of homeless persons. Nurses need to include cultural elements in their work processes, promoting bonding and understanding the ways of life of homeless persons.